Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica (Dataset) ... - Løvlie, Reidar (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica ...